Urbanism Laboratory for cities and regions : Progress of research issues in urbanism 2007 - Hoeven, F.D. Van der (IOS Press, 2013)
The conditions of urban development are currently changing radically. Technological transformations such as automation and robotization in industrial production are leading to new operating conditions for businesses and employees. New transportation and distribution systems are changing the scale and flow patterns of the urban agglomerations. The effects of the general application of information and communication technologies in everyday life are barely to overlook. Globalization and internationalization as well as the processes of European unification have led to increasing competition between urban agglomerations on European and world scales. On the other hand, the social contrasts within these agglomerations are growing. World-wide environmental problems, the necessity for a more efficient use of energy and natural resources as well as a limitation of CO2 emissions mean that we have to make adaptations to our urban structures and building fabric